Natamycin in genital candidosis in men. Issue 3 (June 1975) - Masterton, G; Sengupta, S M; Schofield, C B
Abstract : In a trial of natamycin, an antifungal antibiotic in a vanishing cream base, assessment was possible in 66 men with genital or anal candidosis. The overall cure rate was 82 percent, In 43 patients with culturally proven candidosis it was 98 percent. but in 23 patients treated solely on clinical impression it was only 52 percent. Symptoms were rapidly relieved in those who responded and there were no side-effects. In our hands, natamycin 2 per cent cream has proved to be a valuable preparation in the treatment of candidal balanitis.